2014
DOI: 10.4236/ojtr.2014.23015
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Level and Adult Saudi Health Related Quality of Life

Abstract: Purpose: Physical inactivity in Saudi Arabia is a growing challenge to public health. This study aimed to define the relationship between the physical activity level (PAL) and adult Saudi healthrelated quality of life (HRQoL). Methods: Participants of this study were 100 Saudi adult aged from 18 -70 years. The 36-Item Short-Form Health Status Survey (SF-36) was used to measure the participant's HRQoL. The SF-36 is comprised of 8 domains. The electronic version of the General Practice Physical Activity Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The present research demonstrates that compared to non-exercising almost all levels of PA had positive effects on PCS and MCS. These results were consistent with the literature that usually speculated the varying positive associations of exercise/PA with overall quality-of-life [16, 18, 45, 46], PCS [10, 30, 4650], MCS [10, 11, 30, 47], or subjective well-being [27, 28, 51, 52].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present research demonstrates that compared to non-exercising almost all levels of PA had positive effects on PCS and MCS. These results were consistent with the literature that usually speculated the varying positive associations of exercise/PA with overall quality-of-life [16, 18, 45, 46], PCS [10, 30, 4650], MCS [10, 11, 30, 47], or subjective well-being [27, 28, 51, 52].…”
Section: Discussionsupporting
confidence: 92%
“…Wicker and Frick [27] suggested that light-intensity PA would be beneficial for improving individuals’ mental health too. However, some past research found the insignificant relationship between PA and role limitations due to emotional problems [11, 50]. Therefore, all levels of PA would have varying influences on MCS and its domains, including irregular exercise.…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed the data of researchers (Granero-Jiménez et al, 2022) regarding the close correlation between the physical activity level and psychological well-being of the study participants. Also, our research results complement the data reported by Sobkey (2014). A study involving 100 participants aged from 18 to 70 revealed a positive association between physical activity and health-related quality of life that was measured with the Short Form Health Survey (SF-36) in 4 domains, including physical functioning, role limitations due to physical health problems, vitality, and general health (Kokandi et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…A physical activity index can be computed and categorized as active, moderately active, moderately inactive, and inactive. [ 20 , 21 ]. The levels of serum calcium, phosphorous, and alkaline phosphatase (ALP) were measured as biochemical indicators of bone turnover.…”
Section: Methodsmentioning
confidence: 99%